2018
DOI: 10.1017/s0025315418001121
|View full text |Cite
|
Sign up to set email alerts
|

Colonization dynamics of periphytic ciliates at different water depths in coastal waters of the Yellow Sea, northern China

Abstract: The colonization features of ciliate communities have proved to be a useful tool for indicating water quality status in aquatic ecosystems. To determine an optimal water depth for bioassessment using these ecological bioindicators, the colonization process of periphytic ciliates was studied at four depths of 1, 2, 3.5 and 5 m in Chinese coastal waters. Samples were collected at time intervals of 3, 7, 10, 14, 21 and 28 days using glass slides. The periphytic ciliate communities represented similar colonization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…This suggests that colonization by periphytic ciliate communities is influenced by variations in food supply that, in turn, is correlated with physical-chemical conditions, e.g., sunlight, nutrients, etc., at different depths in the water column. Using distance-based redundancy analysis ordinations, Sikder et al (2019a) demonstrated that the colonization process at 1 m depth occurs in three separate stages ( Fig. 6) which is consistent with earlier reports such as Bamforth (1982), Mieczan (2010), Xu et al (2009a, b), and Zhang et al (2012Zhang et al ( , 2013.…”
Section: Vertical Variation In Colonization Dynamicssupporting
confidence: 90%
See 4 more Smart Citations
“…This suggests that colonization by periphytic ciliate communities is influenced by variations in food supply that, in turn, is correlated with physical-chemical conditions, e.g., sunlight, nutrients, etc., at different depths in the water column. Using distance-based redundancy analysis ordinations, Sikder et al (2019a) demonstrated that the colonization process at 1 m depth occurs in three separate stages ( Fig. 6) which is consistent with earlier reports such as Bamforth (1982), Mieczan (2010), Xu et al (2009a, b), and Zhang et al (2012Zhang et al ( , 2013.…”
Section: Vertical Variation In Colonization Dynamicssupporting
confidence: 90%
“…Furthermore, the colonization curves and the increase in abundance of biofilm-dwelling ciliates and other protozoa closely fitted the MacArthur-Wilson model, and a logistic equation showed differences in functional parameters, i.e., S eq , G and T 90%, representing equilibrium species numbers, colonization rates and the time to 90% S eq , respectively, among different depths in the water column ( Fig. 1a-h; Sikder et al 2019a).…”
Section: General Features Of Colonization Dynamicssupporting
confidence: 57%
See 3 more Smart Citations